2014
DOI: 10.1002/phy2.225
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of adipose tissue and vascular inflammatory gene expression by chronic systemic inhibition of NOS in lean and obese rats

Abstract: We tested the hypothesis that a decrease in bioavailability of nitric oxide (NO) would result in increased adipose tissue (AT) inflammation. In particular, we utilized the obese Otsuka Long Evans Tokushima Fatty rat model (n = 20) and lean Long Evans Tokushima Otsuka counterparts (n = 20) to determine the extent to which chronic inhibition of NO synthase (NOS) with Nω‐nitro‐l‐arginine methyl ester (L‐NAME) treatment (for 4 weeks) upregulates expression of inflammatory genes and markers of immune cell infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
2
13
0
1
Order By: Relevance
“…The link between NO and ET-1 (Alonso & Radomski, 2003) is also supported by recent data from our group demonstrating that chronic systemic NOS inhibition in rats increases expression of ET-1 in the aorta (Fig. 5; Padilla et al 2014). Furthermore, we found in rats that cessation of wheel running for 7 days, and thus removal of the vascular shear stimulus, increases expression of ET-1 in arteries that perfuse the hindlimbs (e.g.…”
Section: Role Of Shear Stress In Mediating Positive Effects Of Habitusupporting
confidence: 71%
See 2 more Smart Citations
“…The link between NO and ET-1 (Alonso & Radomski, 2003) is also supported by recent data from our group demonstrating that chronic systemic NOS inhibition in rats increases expression of ET-1 in the aorta (Fig. 5; Padilla et al 2014). Furthermore, we found in rats that cessation of wheel running for 7 days, and thus removal of the vascular shear stimulus, increases expression of ET-1 in arteries that perfuse the hindlimbs (e.g.…”
Section: Role Of Shear Stress In Mediating Positive Effects Of Habitusupporting
confidence: 71%
“…5; Padilla et al 2014). Furthermore, we found in rats that cessation of wheel running for 7 days, and thus removal of the vascular shear stimulus, increases expression of ET-1 in arteries that perfuse the hindlimbs (e.g.…”
Section: Role Of Shear Stress In Mediating Positive Effects Of Habitumentioning
confidence: 99%
See 1 more Smart Citation
“…Over-expression of constitutive forms of NOS in adipose tissue has been demonstrated to prevent diet-induced obesity, whereas an increase of the inducible NOS seems to enhance both adipocyte size and inflammation [23]. Recent studies have demonstrated that NOS seems to regulate inflammatory genes expression in adipose tissue [24, 25] and the inhibition of its activity has been demonstrated to promote adipose tissue inflammation[26, 27]. …”
Section: Discussionmentioning
confidence: 99%
“…44 NOS inhibitors such as L-NAME (N ω nitro-L-arginine methyl ester), lowered endogenous nitric oxide production and reduced circulating levels of nitric oxide metabolites, 47,48 but had inconsistent effects on the development of obesity and metabolic dysfunction. [47][48][49][50][51] eNOS -/-mice lack endothelial nitric oxide synthase (eNOS) activity, and have an impaired capacity to produce nitric oxide and its metabolites in the cardiovascular system. 52 Besides being hypertensive, these mice have defective energy expenditure, increased white fat accumulation, exhibit insulin resistance and increased hepatic triglyceride levels.…”
Section: Nitric Oxide-dependent Effectsmentioning
confidence: 99%